Elemental Concentration and Pollution in Soil, Water, and Sediment - Romero-Freire, Ana; Qiu, Hao (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book, entitled "Elemental Concentration and Pollution in Soil, Water, and Sediment", presents an updated overview of the main trace elements in living organisms. This collection brings researchers from different fields together, including those from biogeochemistry and ecotoxicology in various environmental media, in order to provide a more comprehensive understanding of the environmental fate of trace elements in their biogeochemical cycles for different ecosystems.